Pengaruh Brand Ambassador Idol Kpop Dan Brand Image Terhadap Keputusan Pembelian Pada E-Commerce Shopee - Bela Ayu Pramudita; Nur Hidayati; Ita Athia (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine the effect of kpop idol brand ambassadors and brand image on purchasing decisions on e-commerce Shopee. The population of this study were students in the city of Malang which consisted of 3 universities, namely the Islamic University of Malang (UNISMA), University of Muhammadiyah Malang (UMM), State University of Malang (UM). The sampling technique used the non-probability sampling method with the snowball sampling technique with a total sample of 70 respondents. This research uses quantitative methods. The results of the study show that simultaneously the brand ambassador variable and brand image variable have a significant effect on purchasing decisions on Shopee e-commerce. Based on the results of the partial test, it shows that kpop idol brand ambassadors have a significant effect on purchasing decisions and brand image has a significant effect on purchasing decisions. Keywords: Brand Ambassador, Brand Image, Purchase Decision